2022
DOI: 10.3389/fcell.2022.760509
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cardiac CircRNAs in Mice With CVB3-Induced Myocarditis

Abstract: Background: Viral myocarditis could initiate various immune response to the myocardium, resulting in myocyte damage and subsequent cardiac dysfunction. The expression profile and functions of circRNAs in this process are unknown.Methods: Fulminant myocarditis (FM) and non-FM models were induced by coxsackie B3 virus (CVB3) infection in A/J mice and C57BL/6 mice, respectively. CircRNAs expression profile was identified by RNA-seq. Quantitative RT-PCR, Spearman rank correlation, KEGG pathway, GO analysis, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…This suggested that lncRNA ROR plays an important role in chronic VMC [ 62 ]. Differential expression of circRNAs has been found in patients with fulminant myocarditis and in mice, and a bioinformatics analysis revealed the involvement of severely dysfunctional immune signaling pathways, including TNF and T-cell receptors, in VMC [ 76 , 77 ]. Compared to miRNAs, other lncRNAs and circRNAs, ncRNAs have not been studied in detail in the field of mechanistic development of VMC and may be potential biomarkers and therapeutic targets for VMC in the future.…”
Section: Ncrnas and Other Factors Associated With Cardiac Fibrosismentioning
confidence: 99%
“…This suggested that lncRNA ROR plays an important role in chronic VMC [ 62 ]. Differential expression of circRNAs has been found in patients with fulminant myocarditis and in mice, and a bioinformatics analysis revealed the involvement of severely dysfunctional immune signaling pathways, including TNF and T-cell receptors, in VMC [ 76 , 77 ]. Compared to miRNAs, other lncRNAs and circRNAs, ncRNAs have not been studied in detail in the field of mechanistic development of VMC and may be potential biomarkers and therapeutic targets for VMC in the future.…”
Section: Ncrnas and Other Factors Associated With Cardiac Fibrosismentioning
confidence: 99%